Birds visiting flowers of the Yellow Ipe (Handroanthus vellosoi) in the urbanized area emphasizes the importance of plant-animal interaction in the afforestation of cities (Research, Society and Development, 2021)
Urban afforestation minimizes the negative impacts of cities on biodiversity. However, afforestation of cities needs to be effective in promoting and maintaining biodiversity and a plant-animal interaction approach seems consistent for this purpose. Through an active search for flowering Yellow-Ipe (Handroanthus vellosoi, Bignoniaceae) trees, and observation of their crowns, we detected 31 bird species from a broad taxonomic and trophic spectrum, visiting their flowers in the urban and peri-urban areas of a city in Brazil. The birds, highlighting six hummingbird species (specialized pollinators), consumed nectar and petals regardless of the flower crops in the tree crown, probably in response to the scarcity of flowers, ripe fleshy fruits, and even insects in the dry season. Species richness estimates suggest that another 11 avian taxa may be associated with the flowers of H. vellosoi. A Principal Component Analysis based on different diversity indices further revealed that H. vellosoi has a high importance value for the floral visiting bird community of various bignoniaceous plants in urban areas. The plant-animal interaction indicates that the planting of H. vellosoi effectively promotes and maintains birds, including ecological functions in cities, e.g., pollination by hummingbirds. Ultimately, plant-animal interactions provide a background for consistently planning, creating, and restoring urban greenery toward nature-friendly cities.